Hydrothermal Synthesis of Nanocomposites Combining Tungsten Trioxide and Zinc Oxide Nanosheet Arrays for Improved Photocatalytic Degradation of Organic Dye - Chien-Yie Tsay; Tao-Ying Hsu; Gang-Juan Lee; Chin-Yi Chen; Yu-Cheng Chang; Jing-Heng Chen; Jerry J. Wu (Nanomaterials)
Both tungsten trioxide (WO3) nanosheet arrays and tungsten trioxide/zinc oxide (WO3/ZnO) nanocomposites were grown on fluorine-doped tin oxide (FTO) coated glass slides using a hydrothermal method to develop a visible-light-driven photocatalyst with easy reusability. Field emission scanning electron microscopy (FE-SEM) observations confirmed the formation of irregular oxide nanosheet arrays on the FTO surfaces. X-ray diffraction (XRD) analysis revealed the presence of hexagonal WO3 and wurtzite ZnO crystal phases. UV-Vis diffuse reflectance spectroscopy showed that integrating ZnO nanostructures with WO3 nanosheets resulted in a blue shift of the absorption edge and a reduced absorption capacity in the visible-light region. Photoluminescence (PL) spectra indicated that the WO 0.5/ZnO 2.0 sample exhibited the lowest electron-hole recombination rate among the WO3/ZnO nanocomposite sample. Photocatalytic degradation tests demonstrated that all WO3/ZnO nanocomposite samples had higher photodegradation rates for a 10 ppm methylene blue (MB) aqueous solution under visible-light irradiation compared to pristine WO3 nanosheet arrays. Among them, the WO 0.5/ZnO 2.0 sample showed the highest photocatalytic efficiency. Furthermore, it exhibited excellent recyclability and high photodegradation stability over three cycles.